Perancangan Interior Belleza Aesthetic Dengan Konsep Modern Natural - Deandra Neva Tessalonika; Syahnas Paradita, Dea; Tri Hastusti Hasana, Henny (JURNAL ASSOSIATIV, 2025)
Belleza Aesthetic is a beauty clinic located in the Kratonan district, Central Java. The beauty clinic that will be established provides a variety of services for women and men ranging from special treatments, salons, nail art, dental treatments, and coffee shops located on the third floor. This research aims to design the layout of Belleza Aesthetic interior elements in order to optimize the function of the space with a modern natural concept. The research method is through data collection methods, interviews, and searching for literature studies. From the results of the research method, it can be concluded that the concept of Moderrn Natural is applied to Belleza Aesthetic with its use being employees and patients of the beauty clinic. The Modern Natural concept is applied to space, walls, floors, ceilings, funiture, and colors. The Modern Natural concept describes a comfortable, warm, and elegant impression. Keywords : Interior Design, Modern Natural, Belleza Aesthetic